Pengaruh Harga terhadap Keputusan Pembelian Ice Cream (Studi Kasus di Mixue Yogyakarta) - Ika Tirta Candra Rini; Agung Hartadi (Jurnal Bisnis, Manajemen, dan Akuntansi, 2023)
Mixue is a drink outlet from China, which serves a variety of drink menus and also ice cream. This drink has so many branches spread across every provincial city and has quite a few fans, so the company must be really careful in setting prices that suit people's pockets. The aim of this research is to find out how influential price is on the decision to purchase Mixue products. This research uses a quantitative research method where data is collected using a questionnaire distributed to 100 respondents who are consumers of ice cream mixue products. Data collection in this research was carried out by distributing questionnaires and then processing them using simple linear regression analysis, T test, and correlation coefficient test. Based on the research results, it shows that price influences the decision to purchase Ice Cream Mixue products. This can be seen from the significance value of 0.001 < 0.05. Keywords: Price, Purchase Decision, Mixue products